THE EFFECT OF GIVING COMPOSE OF WEEDS ON THE GROWTH OF PALM OIL SEEDS (Elaeis guineensis. Jacq) in Pre-Nursery - ENITA; BANGUN JOKO LAKSONO; MUHAMMAD EKO NUGROHO (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2020)
The study aims to determine the impact of a compost dose on plam seed growht and to determine the ideal dosage for plam seed growth. The research out in the experimental garden of Graha Karya College of Agriculture, Muara Bulian Batanghari Jambi province, the research was conducted for three months starting, from October 1, 2019 to December 31, 2019. The research was conducted using Randomized Block Design (RBD) with 6 treatments 4 replications. The treatment is compost consisting of. K1 = Dose of 100 Gram per polybag, K2 = Dose of 200 Gram per polybag, K3 = Dose of 300 Gram per polybag, K4 = Dose of 400 Gram per polybagbag K5 = Dose of 500 Gram per polybag, K6 = Dose of 600 Gram per polybag. In this study there were 6 treatments in the study area, each treatment was repeated 4 times, so that obtained 24 plots or plot plots. Variables observed were sprout growth, number of leaves, leaf length, leaf width and plant height, then the observation data were statistically analyzed using analysis of variance and followed by DNMRT (Duncan New Multiple Range Test) test α 5%. The results showed that the dose of compost from weeds significantly affected the growth of sprouts, leaf length, leaf width and plant height but did not significantly affect the number of leaves of oil palm seedlings in pre-nursery. Compost doses of 100 g weeds provide the best growth for oil palm seedlings in pre-nursery.